1995
DOI: 10.1021/j100007a056
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Study of the Thermochemistry of Molecules in the Si-O-H-C System

Abstract: A self-consistent set of thermochemical parameters for more than 30 molecules in the Si-0-H-C system are obtained from a combination of ab initio electronic structure calculations and empirical corrections. Heats of formation are estimated for another 15 species. The species are primarily methoxy-and ethoxysilicon compounds, including both stable and radical species as well as a few transition states. In the few cases where comparisons with experimental data in the literature are possible, there is good agreem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
63
1
1

Year Published

1997
1997
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(76 citation statements)
references
References 10 publications
11
63
1
1
Order By: Relevance
“…The thermodynamic data for these compounds were obtained from theoretical studies of the literature. [38,39] It was found that the only species that may be present at equilibrium in relatively high mole fractions at temperatures above 1300 K are Si(OH) 4 , SiH(OH) 3 , and SiOSiO. When these three species were not considered, the results were found to be almost identical to those shown in Figure 1 (for SiO 2 deposition) and Figures 3 and 4 (for co-deposition) over the whole temperature range.…”
Section: Gas Phase Equilibrium Resultsmentioning
confidence: 99%
“…The thermodynamic data for these compounds were obtained from theoretical studies of the literature. [38,39] It was found that the only species that may be present at equilibrium in relatively high mole fractions at temperatures above 1300 K are Si(OH) 4 , SiH(OH) 3 , and SiOSiO. When these three species were not considered, the results were found to be almost identical to those shown in Figure 1 (for SiO 2 deposition) and Figures 3 and 4 (for co-deposition) over the whole temperature range.…”
Section: Gas Phase Equilibrium Resultsmentioning
confidence: 99%
“…However, oxygen loss and excessive carbon loss, while not unprecedented20212223, are not common. Previous studies on the bond dissociation energies of TEOS and similar compounds reveal that the dissociation of organometallic compounds to form oxygen containing gases requires higher energy than simply breaking C-H bonds242526. This may explain the higher oxygen and carbon loss as a result of increasing ion energy and fluence, and thus an increase in the total deposited energy.…”
Section: Resultsmentioning
confidence: 98%
“…In the Supporting Information (Tables S7 -S11), we also provide raw electronic energies at the G2 level, atomic coordinates, vibrational frequencies, moments of inertia, and polynomial fits of the thermodynamic data suitable for use with the CHEMKIN software. 17 As has been typical in previous publications involving the BAC-MP4 series, 15,16,[18][19][20][21][22][23][24][25] we focus our discussion on the predicted thermochemical parameters, rather than on the ab initio calucations themselves. .…”
Section: Amentioning
confidence: 99%